Differentiated Learning In Islamic Religious Education Subject In Improving Students' Creativity - Ningsih, Titik; Sit, Masganti; Rakhmawati, Fibri (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Differentiated learning activities prioritize the willingness and comfort of students. With the implementation of differentiated learning through the independent curriculum, it is hoped that the education system will be able to produce students who think critically, creatively, and innovatively so that they can work in teams and compete in the 4.0 era towards the 5.0 revolution. Differentiated Learning Activities to adjust students' learning interests in the learning process. Learners are free to choose and express ideas and information that match their interests in the learning process. This diversity of learning interests is one of the important elements that educators need to observe so that the needs of individual learners will be met and produce high learning outcome goals through this differentiated learning activity. The method used in this research is descriptive qualitative with a case study approach. This method not only illustrates events that have occurred but also analyzes the meaning of the phenomena that occur so that it rests on a complete understanding. The types of data analysis used are Data reduction, Data display, and Conclusion/verification. Triangulation of participants, member checking, and extended observation were carried out to check the validity of the data. After the application of differentiated learning activities, it is known what are the challenges and obstacles to differentiated learning activities at SMAN 7 Binjai.